2018
DOI: 10.1007/s40520-018-0939-4
|View full text |Cite
|
Sign up to set email alerts
|

Does 1.5 T mpMRI play a definite role in detection of clinically significant prostate cancer? Findings from a prospective study comparing blind 24-core saturation and targeted biopsies with a novel data remodeling model

Abstract: In patients with suspected PC and a previous negative PBx, a normal mpMRI may exclude a clinically significant PC, avoiding sPBx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…In 70.4% of all patients (343/487) where there was at least one lesion of PI-RADS ≥3, using 24 core SB as the reference, MRI-TB had a negative predictive value of 92% and 99% for csPC defined as GG ≥2 or GG ≥3, respectively [35]. These results have been confirmed by several studies [36][37][38][39][40], ans a summary can be found in Table 3. Many clinical societies have since included a recom-mendation for performing mpMRI after an initial negative SB and persistent suspicion for PC [14].…”
Section: Patients With Negative Systematic Biopsy and Persistent Suspmentioning
confidence: 52%
“…In 70.4% of all patients (343/487) where there was at least one lesion of PI-RADS ≥3, using 24 core SB as the reference, MRI-TB had a negative predictive value of 92% and 99% for csPC defined as GG ≥2 or GG ≥3, respectively [35]. These results have been confirmed by several studies [36][37][38][39][40], ans a summary can be found in Table 3. Many clinical societies have since included a recom-mendation for performing mpMRI after an initial negative SB and persistent suspicion for PC [14].…”
Section: Patients With Negative Systematic Biopsy and Persistent Suspmentioning
confidence: 52%
“…In summary, on a patient basis, the primary mpMRI has a negative predictive value (NPV) of 88% for PC and Gleason score of ≥3 + 4 [ 7 ]. This can be improved in cases with previous negative systematic biopsy to an NPV of 91–100% [ 11 , 12 , 13 ]. The capabilities come with some important limitations.…”
Section: Introductionmentioning
confidence: 99%